2014
DOI: 10.3810/pgm.2014.07.2790
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Acute Hypertension in Patients With Renal Dysfunction: Labetalol or Nicardipine?

Abstract: Within 30 minutes of administration, nicardipine is more efficacious than labetalol for acute blood pressure control in patients with RD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
5
2
1
Order By: Relevance
“…We found that cancer and renal disease were the two common causes of hypertensive crisis as described in other studies [ 14 , 15 ]. Our study also exhibited that there was no difference between nicardipine and labetalol in the treatment of hypertensive crisis, which differed from the result of an adult study that showed nicardipine to be more efficacious within 30 minutes than labetalol in patients with renal dysfunction [ 16 ]. However, Thomas et al also reported no significant difference of efficacy between nicardipine and labetalol in infants and small children with a hypertensive crisis [ 17 ].…”
Section: Discussioncontrasting
confidence: 83%
“…We found that cancer and renal disease were the two common causes of hypertensive crisis as described in other studies [ 14 , 15 ]. Our study also exhibited that there was no difference between nicardipine and labetalol in the treatment of hypertensive crisis, which differed from the result of an adult study that showed nicardipine to be more efficacious within 30 minutes than labetalol in patients with renal dysfunction [ 16 ]. However, Thomas et al also reported no significant difference of efficacy between nicardipine and labetalol in infants and small children with a hypertensive crisis [ 17 ].…”
Section: Discussioncontrasting
confidence: 83%
“…16 Nicardipine infusion has been shown to reduce blood pressure toward this goal more rapidly, while producing less BPV than intravenous push (IVP) antihypertensive medication. [27][28][29] Although our study did not identify BPV as an independent risk factor for the outcome of mortality among patients with sICH, we identified one EPs' intervention that was associated with patients' in-hospital mortality. Starting nicardipine infusion in the ED was associated with 65% lower likelihood of death for patients.…”
Section: Discussioncontrasting
confidence: 62%
“…En cuanto a la etnia, se ha visto que la mayor predisposición a desarrollar enfermedades hipertensivas se presenta en afrodescendientes, datos corroborados por Varon et al, (Asturias-España, 2015), en una investigación realizada con 104 pacientes [10]. En contraposición, en el presente estudio la totalidad de individuos correspondieron a la etnia mestiza, pues resultó dificultoso involucrar en el estudio pacientes afrodescendientes, datos respaldados por uno de los últimos censos dados por el INEC, 2010, en el cual, el 89.6% de la población azuaya se identifica como mestiza [11].…”
Section: Discussionunclassified